The influence of different metal-chelate conjugates of pentixafor on the CXCR4 affinity - Poschenrieder, Andreas (EJNMMI Res, 2016)
BACKGROUND: The overexpression of the chemokine receptor 4 (CXCR4) in different epithelial, mesenchymal, and hematopoietic cancers makes CXCR4 an attractive diagnostic and therapeutic target. However, targeting the CXCR4 receptor with small cyclic pentapeptide-based radiopharmaceuticals remains challenging because minor structural modifications within the ligand-linker-chelate structure often significantly affect the receptor affinity. Based on the excellent in vivo properties of CXCR4-directed pentapeptide [(68)Ga]pentixafor (cyclo(-d-Tyr-N-Me-d-Orn(AMB-DOTA)-l-Arg-l-2-Nal-Gly-)), this study aims to broaden the spectrum of applicable (radio)metal-labeled pentixafor analogs. METHODS: Cyclic pentapeptides, based on the pentixafor scaffold, were synthesized by a combined solid- and solution-phase peptide synthesis. The CXCR4 receptor affinities of the cold reference compounds were determined in competitive binding assays using CXCR4-expressing Jurkat T - cell leukemia cells and [(125)I]FC131 as the radioligand. RESULTS: Metalated pentixafor derivatives with cyclic and acyclic chelators were synthesized by solid-phase peptide synthesis and evaluated in vitro. The resulting CXCR4 affinities (IC(50)) were highly dependent on the chelator and metal used. Two pentapeptides, Ga-NOTA and Bi-DOTA conjugates, offer an improved affinity compared to [(68)Ga]pentixafor. CONCLUSIONS: Based on the pentapeptide [(68)Ga]pentixafor, a broad range of metal-labeled analogs were investigated. The affinities of the new compounds were found to be strongly dependent on both the chelator and the metal used. Bi-labeled pentixafor showed high receptor affinity and seems to be a promising ligand for further preclinical evaluation and future α-emitter-based endoradiotherapy.